Role of Secondary Brain Damage Factors in Activation of VascularPlatelet Hemostasis in Traumatic Brain Injury - G. A. Boyarinov; L. V. Boyarinova; A. V. Deryugina; O. D. Solov'eva; R. R. Zaytsev; O. V. Voyennov; E. V. Moshnina; A. V. Shumilova (Общая реаниматология)
Purpose of the study. To evaluate the role of secondary brain damage factors in activation of vascularplatelet hemostasis in traumatic brain injury (TBI).Material and methods. In the ICU, 30 patients with complex traumatic brain injury were examined and treated. In the posttraumatic period, in patient measurement of heart and vascular tone, platelets, hemoglobin, lactate, and active forms of oxygen in the blood were investigated.The study results have showed that damaged brain secondary factors accompanying concomitant TBI (circulatory insufficiency, hypoxia, acidosis and increased free radical formation) represent at the same time nonspecificstimuli for platelets and cells of blood vessels that consequently, cause systemic activation of the vascularplatelet link within the hemostasis system.Conclusion. Nonspecific systemic activation of the vascularplatelet hemostasis by secondary factors in the patients with concomitant TBI is one of pathogenetic components of ischemic brain damage.